Al-Hanin fi Muwashshahat “Jadaka al-Ghaythu” li-Lisan al-Din ibn al-Khatib: Dirasah Dalaliyyah: Longing in Lisan al-Din ibn al-Khatib’s Muwashshaha “Jadaka al-Ghayth”: A Semantic Study - Ikram Azmi; Fahmi Sofyan; Anshar Zulhelmi (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2026)
Although the muwashshaḥ Jādaka al-Ghayth by Lisān al-Dīn Ibn al-Khaṭīb has been extensively studied from literary, historical, and phonological perspectives, its semantic construction of ḥanīn (longing) through Ahmad Mukhtar 'Umar's semantic theory remains largely unexamined. This study analyzes how the meaning of ḥanīn is constructed in the muwashshaḥ using Ahmad Mukhtar 'Umar's semantic framework. Employing a qualitative descriptive method, the study examines eight selected verses containing explicit or implicit lexical markers of ḥanīn, classified according to five semantic categories: basic, additional, Affective, suggestive, and stylistic meaning. The findings show that ḥanīn is not merely an emotional expression but a composite semantic structure built through the interrelation of four functional dimensions: historical-spatial reference, natural symbolism, psychological affect, and rhetorical strategy. This relational structure reconstructs the Andalusian past as an idealized space set against the poem's experience of loss. The study demonstrates the applicability of Ahmad Mukhtar 'Umar's semantic theory to classical Arabic poetry and offers a systematic semantic model for interpreting ḥanīn, with implications for both semantic scholarship and the teaching of critical literary reading. على الرغم من أن موشحة